Avaliação parasitológica de alfaces (Lactuca sativa l.) comercializadas no município de Itaqui, RS - (:unkn) unknown (Universidade Federal do Pampa, 2013)
The consumption of lettuce (Lactuca sativa) may be an important mode of transmission of various parasitic diseases. The parasitological control is a major challenge, even when there is increasing inclusion of vegetables in the diet of the population. The aim of this study was to evaluate the contamination by parasites of interest in Public Health in lettuce (Lactuca sativa) market in the municipality of Itaqui (RS). Methods: We used a sampling process, selecting supermarkets and local producers in the city of Itaqui RS. We investigated 60 samples of lettuce (Lactuca sativa) crisp variety, and 30 samples from local producers and 30 samples from local markets, all acquired randomly. Was withdrawn lettuce samples from supermarkets and local producers which were packed in polyethylene bags cleaned and identified. The leaves were separated and washed in a sterile glass container with 250 ml distilled water. The water wash was analyzed using three parasitological techniques: direct examination, spontaneous sedimentation technique (Lutz) and flotation zinc sulfate to 33 % (Faust). The morphology of parasites was taken by an optical microscope. Results: of the 60 samples analyzed, 29 (48.33 %) had some type of parasites. Of these, 19 (63.34 %) were collected from local producers and 10 (36.66%) markets. Protozoa and helminthes found in contaminated samples were Giardia lamblia (38%), Entamoeba sp (13%) and Ascaris lumbricoides (5%). Conclusions: checking for the presence of parasites, especially helminthes and protozoa, especially in vegetables, have great interest to public health because it provides subsidies for the health monitoring of the hygienic state of these products.
Keywords: Parasitologia; Alface; Controle higiênico-sanitário; Alimento; Parasitology; Lettuce; Sanitary-hygiene control; Food; CNPQ::CIENCIAS DA SAUDE